Integrasi Dakwah Agama, Kehumasan, Dan Narasi Politik Lalu Muhammad Iqbal: Studi Netnogragi Di Media Sosial Instagram - M. Roby Satriawan (Jurnal Khabar: Komunikasi dan Penyiaran Islam, 2026)
This study aims to critically examine the integration of religious outreach (*dakwah*), public relations, and political narratives in Lalu Muhamad Iqbal’s digital communication practices on Instagram, employing a netnographic approach. Utilizing a qualitative method with a netnographic design, the research focuses on analyzing digital content, visual representations, captions, and audience interactions on the subject's Instagram account. Data were collected through non-participant observation, digital documentation, and literature review, then analyzed using thematic and critical discourse analysis to uncover underlying patterns of meaning, symbolic practices, and power relations inherent in the communication process. The findings reveal that the integration of religious outreach, public relations, and political narratives creates a hybrid communication model characterized by symbolic, performative, and strategically curated representations. Religious expressions serve to establish moral legitimacy, public relations elements foster emotional closeness with the audience, and political narratives are conveyed implicitly through visuals of work activities and governance. The study suggests that digital platforms function not merely as communication tools but also as arenas for symbolic power and the production of meaning. Furthermore, the research highlights the need for adaptive, reflective, and inclusive communication strategies that acknowledge audience agency and the complexities of the digital public sphere.